Evaluating the Potential Safety Risk of Plant-Based Meat Analogues by Analyzing Microbial Community Composition - Dan Hai; Baodang Guo; Mingwu Qiao; Haisheng Jiang; Lianjun Song; Ziheng Meng; Xianqing Huang (Foods, 2023)
Plant-based meat analogues offer an environmentally and scientifically sustainable option as a substitute for animal-derived meat. They contribute to reducing greenhouse gas emissions, freshwater consumption, and the potential risks associated with zoonotic diseases linked to livestock production. However, specific processing methods such as extrusion or cooking, using various raw materials, can influence the survival and growth of spoilage and pathogenic microorganisms, resulting in differences between plant-based meat analogues and animal meat. In this study, the microbial communities in five different types of plant-based meat analogues were investigated using high-throughput sequencing. The findings revealed a diverse range of bacteria, including Cyanobacteria, Firmicutes, Proteobacteria, Bacteroidota, Actinobacteriota, and Chloroflexi, as well as fungi such as Ascomycota, Basidiomycota, Phragmoplastophyta, Vertebrata, and Mucoromycota. Additionally, this study analyzed microbial diversity at the genus level and employed phenotype prediction to evaluate the relative abundance of various bacterium types, including Gram-positive and Gram-negative bacteria, aerobic, anaerobic, and facultative anaerobic bacteria, as well as potential pathogenic bacteria. The insights gained from this study provide valuable information regarding the microbial communities and phenotypes of different plant-based meat analogues, which could help identify effective storage strategies to extend the shelf-life of these products.